Behavioral neuroscience of Orexin/Hypocretin - Lawrence, Andrew J. (Professor of behavioural neuroscience); Lecea, Luis de (Springer, 2017)
This issue of Current Topics in Behavioral Neuroscience focuses on the neuropeptide orexin (hypocretin) and brings together scientists from around the world who will provide a timely discussion of how this peptide regulates behavior. This is a fast-moving field, and with the incorporation of novel technologies, new breakthroughs are likely to continue. For example, the use of optogenetic approaches has enabled the identification of the role of orexin-containing neurons in arousal states, critical for higher order functioning. From a clinical perspective, genetic polymorphisms in hypocretin/orexin and orexin receptors are implicated in a number of psychiatric disorders. In addition, advanced clinical trials are currently underway for orexin receptor antagonists in the treatment of insomnia and sleep disorders. We aim to capture a broad audience of basic scientists and clinicians.
Keywords: Orexins.; Neuropsychology.; Neurosciences.; elektronické knihy; electronic books